Inactivation of Herpes Simplex Virus by Thiosemicarbazones and Certain Cations - Levinson, Warren (1974)
We demonstrated that herpes simplex virus types 1 and 2, including a type 2 strain which transforms hamster cells in vitro, and Herpesvirus saimiri are inactivated by exposure to thiosemicarbazones. Because thiosemicarbazones are thought to interact with heavy metals in this inactivation process (9), we tested and found some of these herpesviruses to be susceptible to exposure to certain heavy metals. A virion polymerase was sought because the ribonucleic acid (RNA)-dependent deoxyribonucleic acid (DNA) polymerase of Rous sarcoma virus and the DNA-dependent RNA polymerase of vaccinia virus are inhibited. However, neither DNA nor RNA polymerase activity could be demonstrated in herpes simplex virions. The ability of thiosemicarbazone to ameliorate the course of herpes simplex virus infection in rabbit eyes was observed, but was considered insufficient to be of clinical importance.